Upaya Guru Dalam Penguatan Konsep IPAS Tentang Perubahan Iklim Di SDN 25 Mataram - Tika Rahmatullah; Baiq Nozi Minarni; Mira Febrianti; Adriyan Dwi Putra; Muhammad Anwar Sani (STAI AL-AMIN, 2026)
This study aims to identify teachers' efforts in strengthening IPAS concepts about climate change at SDN 25 Mataram. This study was conducted using a qualitative approach with a case study research design. This study used data collection techniques in the form of observation, interviews, and documentation. The subjects of this study were sixth-grade teachers who taught IPAS and nine sixth-grade students. The results showed that teachers implemented various efforts to strengthen students' understanding of climate change, including providing motivational apersepsi, providing visual media, and applying the Project-Based Learning (PjBL) method, which allows students to learn through direct experience. Teachers also linked the material to weather phenomena and the environment around the school to make the concepts more tangible for students. The obstacles encountered included limited facilities, low student science literacy, and a lack of interactive learning media. Nevertheless, the learning strategies applied by teachers were quite effective in helping students understand the differences between weather and climate and the impact of climate change on daily life. In conclusion, teachers succeeded in strengthening students' understanding of climate change through perception, visual media, and the PjBL method, despite facing obstacles in terms of facilities and science literacy. These strategies remain effective in helping students understand the concepts of weather, climate, and the impacts of climate change.